I put a (mis)spell on you. Erratas, malentendidos e identidades alternas: el caso de Perdita Durango - Kevin Perromat Augustin (Les Cahiers ALHIM)
This essay intends to reflect, focusing on the film by Álex de la Iglesia Perdita Durango (1997) on the use of stereotypes in the fictional representation of cultural identities through diverse discourses, and on the practices of legitimization of the agents that operate in the creation and transmission of such imaginaries. In these processes of influence and transfer, the act of “misspelling” and the production of linguistic and cultural misinterpretations acquire a singular and ambivalent role, which reflects the productivity of misunderstanding in the transfers, from writing, of certain persistent stereotypes in contemporary audiovisual art.